'The right thing to do': Fostering social inclusion for mental health service users through acts of citizenship. (27th August 2018) - Hamer, Helen Paris; Rowe, Michael; Seymour, Carol Ann
Abstract: The theoretical framework of citizenship is increasingly being used in mental health settings to inform practice. This exploratory qualitative study describes in more detail the acts of citizenship embedded in the everyday practices of mental health workers that promote the social inclusion of people in their care. Acts make a claim for justice when one's rights and responsibilities of citizenship are denied. Semistructured interviews were conducted with 12 participants, seven mental health clinicians and five peer support workers, recruited from a mental health facility in Connecticut, USA. Two themes are presented, breaking the rules and the right thing to do, a rights‐based practice that fosters inclusion for service users. Results suggest that staff undertake hidden acts of citizenship to promote inclusion and rights of service users by responsibly subverting the rules and norms of the organization. Changes to organizational practices to make visible such inclusionary acts are required. Implications for practice and considerations of organizational change through the development of a citizenship framework to underpin practice are recommended.